(untitled) (Journal of Hama University, 2022)
This research aims to study and analyze the reality of official development aid obtained by Syria during the period from 2000 to 2020, with the aim of determining whether there is a structural break in the time series of this aid during the studied period and determining the cause of this break, if any, in addition to show whether this aid played an important role, as one of the sources of external funding, in light of the crisis that Syria was exposed to at the beginning of 2011. To achieve this goal, the standard approach was relied on in analyzing the time series data on official development aid obtained from World Bank database. Where the Breakpoint Unit Root Test was used to determine whether there is a structural break in the series of official development aid that Syria obtained during the studied period, and the T-test was used to test the differences between the arithmetic averages of the official development aid obtained by Syria before and after The crisis it was exposed to at the beginning of 2011. This research found a structural break in the official development aid chain that Syria received during the studied period. This break was identified in 2011, the year in which the crisis began in Syria, and this research also found There are substantial differences in the size of official development aid obtained by Syria before and after the crisis, where the results of the T-test showed that the arithmetic mean of the natural logarithm of the official development aid that Syria obtained after the crisis (22.2397), is greater than the arithmetic mean of the natural logarithm of the official development aid that Syria obtained before the crisis (18,4185).